"Judges of the Velum" and "Judges of the Hippodrome" in Thessalonike (11th c.) - Andreas GKOUTZIOUKOSTAS (Byzantina Symmeikta, 2010)
<!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; mso-layout-grid-align:none; punctuation-wrap:simple; text-autospace:none; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; mso-layout-grid-align:none; punctuation-wrap:simple; text-autospace:none; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} p.MsoFootnoteText, li.MsoFootnoteText, div.MsoFootnoteText {mso-style-noshow:yes; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; mso-layout-grid-align:none; punctuation-wrap:simple; text-autospace:none; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} p.MsoHeader, li.MsoHeader, div.MsoHeader {margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; tab-stops:center 207.65pt right 415.3pt; mso-layout-grid-align:none; punctuation-wrap:simple; text-autospace:none; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} p.MsoBodyText, li.MsoBodyText, div.MsoBodyText {margin:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; font-style:italic;} p.BodyText2, li.BodyText2, div.BodyText2 {mso-style-name:"Body Text 2"; margin:0cm; margin-bottom:.0001pt; text-align:justify; text-indent:17.0pt; line-height:13.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; mso-hyphenate:none; mso-layout-grid-align:none; punctuation-wrap:simple; text-autospace:none; font-size:10.5pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:595.3pt 841.9pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1; mso-footnote-position:beneath-text;} --> The present study focuses on judicial officers coming from Constantinople to Thessalonike in the 11th century. The judge of the theme of Thessalonike was in charge of trying cases in the region. From the second fifth of the 11th century, however, his jurisdiction was extended to the greater financial and judicial unit of Boleron, Strymon and Thessalonike as well. Lead seals and documents from the archives of the monasteries of Athos prove that many of the krites of Boleron, Strymon and Thessalonike had been previously krites of the velum and judges of the hippodrome who performed their duties in the capital and belonged to the ranks of the “small judges”. These judicial officers tried cases that were referred to them, while they could also function as assessors of the “great” or superior judges of Constantinople, i.e. the droungarios of the vigla, the dikaiodotes, the protoasecretis, the eparchos of the city, the koiaistor and the epi ton kriseon. The latter could delegate the authority to try cases to the “small” or inferior judges. Consequently, the judges of the velum and the judges of the hippodrome could also be sent from Constantinople to the themes by the emperor or other officials, in order to examine some cases and then return to the capital. This is confirmed by the primary sources, which mention for example the case of judge of the hippodrome Michael Rhodios, who was sent by Alexios I Komnenos in 1084 from Constantinople to the region of Thessalonike, in order to examine a dispute between the Lavra monastery and the brother of the emperor, Adrian. Some years later Michael Rhodios was sent again to try cases in Thessalonike, but this time as krites of Boleron, Strymon and Thessalonike. Consequently, apart from the judge of Boleron, Strymon and Thessalonike, other judges delegated by the emperor or by high officers could also examine cases there, as happened in other themes. From the 14th century on, as Macedonia developed its own law schools, a person who had acquired legal training and judicial experience in Thessalonike could continue his judicial career in Constantinople.